2013
DOI: 10.1115/1.4023383
|View full text |Cite
|
Sign up to set email alerts
|

50 Years of Computer Simulation of the Human Thermoregulatory System

Abstract: This paper presents an updated and augmented version of the Wissler human thermoregulation model that has been developed continuously over the past 50 years. The existing Fortran code is translated into C with extensive embedded commentary. A graphical user interface (GUI) has been developed in Python to facilitate convenient user designation of input and output variables and formatting of data presentation. Use of the code with the GUI is described and demonstrated. New physiological elements were added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Vasodilation occurs progressively above 38 C core temperature. Normothermic perfusion exists for the plateau of states between these thresholds [57]. Hysteresis occurs in transitions to normothermia.…”
Section: Modeling and Simulation Of Thermoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasodilation occurs progressively above 38 C core temperature. Normothermic perfusion exists for the plateau of states between these thresholds [57]. Hysteresis occurs in transitions to normothermia.…”
Section: Modeling and Simulation Of Thermoregulationmentioning
confidence: 99%
“…Figure 5 is a simplified cartoon of the nodal connectedness of the model. The elements for the hands and feet are components added recently to represent the glabrous skin areas and mass of the hands and feet [57].…”
Section: Modeling and Simulation Of Thermoregulationmentioning
confidence: 99%
“…While the majority of research has been conducted on the skin of the forearm, we and others have reported marked regional differences in the mechanisms of control of the vasodilation response to local heating . Thus, if we are to properly understand and appropriately model the role of skin blood flow in thermoregulation, an understanding of both the mechanisms of control and associated regional variations is required.…”
Section: Introductionmentioning
confidence: 99%
“…As stressed by Hensley et al [1] and Havenith and Fiala [2], in recent years there has been a growing demand from industry for robust and reliable models predicting human thermophysiological responses. In several applications is required a detailed analysis of the complex environmental heat transfer processes involving human occupancy in order to design safe, comfortable and energy-efficient buildings, in biomedical applications, in cars, or industrial environments in the presence of heat related injuries and also in military and sport [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%